Analisis Web Performance Load Test Pada Situs Web PT Neptus Teknologi Indonesia Jakarta Setelah Menggunakan Cloud Web Application Firewall (WAF) - Sukmana, Sulaeman Hadi; Saputra, Deri; Puspitasari, Diah; Azizah, Qudsiah Nur; Sikumbang, Erma Delima; Ramanda, Kresna (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2024)
Advances in information technology are increasing over time, the use of the internet has become a daily thing that is often done. All kinds of activities that take place every day some use an internet connection for the process. PT Neptus Teknologi Indonesia currently needs protection for the company's website to improve performance and avoid hacker attacks. Website security protection using Cloud Web Application Firewall (WAF) at PT Neptus Teknologi Indonesia is used to improve website performance which is not currently implemented. Currently, the performance of the company's website still gets insufficient marks in the criteria for a good website in testing using Pingdom Tools and GTMetrix and is not yet protected for security. The stages carried out start from making observations, preparing tools and materials, determining testing tools, installing and configuring the Cloud Web Application Firewall WAF and carrying out testing and data analysis. The results of the analysis that has been carried out show that the use of Cloud Web Application Firewall (WAF) for the performance of the neptus.co.id website is very beneficial because implementing cloud WAF can change the performance load and prevent attacks from hackers